Lower etanercept levels are associated with high disease activity in ankylosing spondylitis patients at 24 weeks of follow-up. Issue 10 (7th May 2014) - Kneepkens, E L; Krieckaert, C L M; van der Kleij, D; Nurmohamed, M T; van der Horst-Bruinsma, I E; Rispens, T; Wolbink, G J
Abstract : Background: Previous data have shown that etanercept levels are associated with clinical response in rheumatoid arthritis. However, for ankylosing spondylitis (AS), data regarding this topic are inconclusive. Objectives: To investigate the relationship between etanercept levels and clinical response in patients with AS. Methods: Observational prospective cohort study of 162 patients with AS =treated with etanercept, monitored during 24 weeks of treatment. Etanercept trough levels were determined, retrospectively, using an ELISA. Disease activity was measured using AS Disease Activity Score (ASDAS), including C-reactive protein (CRP) and Bath AS Disease Activity index (BASDAI). Active disease was defined as ASDAS≥2.1. Since etanercept is a drug administered at home there might have been some variation in trough level sampling. Results: At 24 weeks etanercept levels were significantly higher in patients with ASDAS<2.1, (3.8 mg/L; IQR 2.5–5.2) compared with patients with ASDAS≥2.1 (2.3 mg/L; IQR 1.2–3.4; p≤0.001). Generalised estimating equation analysis demonstrated a statistically significant association between etanercept levels and ASDAS, BASDAI, CRP and erythrocyte sedimentation rate (all p<0.001). When patients were categorised into quartiles according to etanercept levels, the lowest quartile (etanercept<1.80 mg/L) comprised 35% of all patients with ASDAS≥2.1 while the highest quartile comprised only 14%. Conclusions: Disease activity and inflammation are associated with etanercept levels in patients with AS at 24 weeks of treatment. Measuring etanercept levels might help in identifying overtreatment and undertreatment and optimise etanercept therapy in AS.